Long-term follow-up of bilateral gracilis reconstruction following extra-levator abdominoperineal excision. (January 2023) - Jenkins, E.; Humphrey, H.; Finan, C.; Rogers, P.; McDermott, F.G.; Smart, N.J.; Daniels, I.R.; Watts, A.M.
Summary: Introduction: Colorectal operations such as an extra-levator abdominoperineal (elAPE) excision for locally advanced or recurrent cancer create a significant perineal tissue deficit. Options for perineal reconstruction include bilateral pedicled gracilis muscle flaps (BPGMF). Fashioning the gracili into a 'weave' creates a muscular sling that supports pelvic contents and is a novel technique. Our series reports the outcomes of the BPGMF in 50 patients undergoing surgery for pelvic cancer. Method: This is a retrospective, single-centre study of patients undergoing reconstruction of perineal defects using BPGMF. All surgeries took place between January 2008 and February 2021. The primary outcome measured was perineal wound healing. The secondary outcomes measured were complications of surgical sites and length of hospital stay (short term), flap integrity on follow-up imaging and functional outcomes (long term). Results: Fifty patients underwent perineal reconstruction using BPGMF (26 males). The median age was 62 years. The 30-day mortality was 2% ( n  = 1). The average follow-up period was 2 years. Complete perineal wound healing was 86% (42/49) at outpatient follow-up. Complication rates for the donor site and reconstructed site were 14% and 22%, respectively. Complications included infection (2% donor site, 12% perineum), haematoma (4% donor site), dehiscence (2% donor site, 4% perineum) and seroma (3% donor site, 2% perineum). Conclusion: BPGMF offers a reliable and technically simple muscle flap to reconstruct large perineal defects. The muscle flap integrity appears maintained on follow-up imaging despite a lack of flap monitoring tools. This cohort had minimal functional impairment following BPGMF.